Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan E-Commerce Shopee - Tisya Patience; Sarah Azizah; Angelica Cristy; Rona Dearta (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of service quality on customer satisfaction with Shopee e-commerce. The research method used is Quantitative Research Method, using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, simultaneous test (f), partial test (t), and coefficient of determination test (R²). This study obtained primary data using a questionnaire distributed to 75 respondents who are Shopee e-commerce users. The results showed that service quality (X1) and product quality (X2) had a positive and significant effect on customer satisfaction (Y) among Shopee e-commerce users. The t-test showed that the values of both variables were below 0.05, indicating that the better the service quality and product quality, the higher the level of customer satisfaction. The F test shows that both independent variables simultaneously and mutually influence each other with a significance value of 0.000<0.05. The coefficient of determination (R²) value of 0.526 indicates that 52.6% of customer satisfaction variation can be explained by service quality and product quality, while the remaining 47.4% is influenced by other factors outside this study. Based on these results, the study shows that fast, accurate, and safe service, as well as products that meet consumer expectations, are important factors in building customer satisfaction on Shopee.